ANALISIS KINERJA PENGELOLAAN KEUANGAN DESA (STUDI PADA KECAMATAN BETUNG KABUPATEN BANYUASIN) - M. Thoyib; Chandra Satria; Septiana Septiana; Darul Amri (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2020)
The purpose of this study was to determine the performance of village financial management in Betung District, Banyuasin District. Data was collected in this study using a questionnaire, the sample used a purposive sampling method, the research unit was the Village Head, Village Secretariat, Village Treasurer or Head of Finance, Section Chief, Head of Village Affairs and Village Consultative Body. The number of samples in this study (each village 8 respondents with a total of 9 villages), the method of analysis using multiple regression with SPSS version 20 calculations As for the results of the study are the Capacity of Village Apparatuses, Village Financial Reporting Words, BPD Supervision Quality and Village Assistance have a positive and significant effect on the performance of village financial management in Betung District, Banyuasin District, both partially and simultaneously.